Gene Therapy in Corneal Transplantation - Qazi, Yureeda (2013)
Corneal transplantation is the most commonly performed organ transplantation. Immune privilege of the cornea is widely recognized, partly because of the relatively favorable outcome of corneal grafts. The first-time recipient of corneal allografts in an avascular, low-risk setting can expect a 90% success rate without systemic immunosuppressive agents and histocompatibility matching. However, immunologic rejection remains the major cause of graft failure, particularly in patients with a high risk for rejection. Corticosteroids remain the first-line therapy for the prevention and treatment of immune rejection. However, current pharmacological measures are limited in their side-effect profiles, repeated application, lack of targeted response, and short duration of action. Experimental ocular gene therapy may thus present new horizons in immunomodulation. From efficient viral vectors to sustainable alternative splicing, we discuss the progress of gene therapy in promoting graft survival and postulate further avenues for gene-mediated prevention of allogeneic graft rejection.